Disagreement in physical activity assessed by accelerometer and self-report in subgroups of age, gender, education and weight status - Seidell Jacob C; Chinapaw Marijke JM; Schuit Albertine J; Slootmaker Sander M; van Mechelen Willem (BMC, 2009)
Abstract Background The purpose of this study is to compare self-reported time (by questionnaire) and objectively measured time (by accelerometer) spent on physical activity at moderate (MPA) and vigorous intensity (VPA) in subgroups of age, gender, education and weight status. Methods In total, 236 adolescents (aged 12-18) and 301 adults (aged 22-40), completed the questionnaire and wore an accelerometer for two weeks. Results Adolescents reported exceptionally more time spent on MPA (mean difference 596 ± 704 min/wk) and VPA (mean difference 178 ± 315 min/wk) than was assessed objectively by the accelerometer. Based on the questionnaire, high educated adolescents spent more time on MPA (205 min/wk, p = 0.002) and VPA (120 min/wk, p = 0.01) than low educated adolescents, but according to the accelerometer they spent less time on MPA (149 min/wk, p = 0.001) and VPA (47 min/wk, p = 0.001). Among adults there was moderate agreement between self-reported time and objectively measured time spent on MPA, but in general the reported time spent on MPA (mean difference 107 ± 334 min/wk) and VPA (mean difference 169 ± 250 min/wk) exceeded the time measured with the accelerometer. Overweight adults reported significantly more VPA (57 min/wk, p = 0.04) than normal weight adults, but this was not confirmed by the accelerometer data. Conclusion We observed large differences in time spent on MPA and VPA measured by questionnaire and accelerometer in adolescents but reasonably good agreement in adults. Differences between methods varied by gender, education and weight status. This finding raises serious questions about the use of questionnaires to quantify MPA and VPA in adolescents. There is a clear need in advanced valid assessments of PA in adolescents. Trial number ISRCTN93896459